2007
DOI: 10.1007/s00395-007-0690-z
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor/c-kit signaling mediated cardiac stem cell migration via activation of p38 MAPK

Abstract: It demonstrated that SCF/c-kit signaling may mediate the migration of CSCs via activation of p38 MAPK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 40 publications
1
78
0
Order By: Relevance
“…In vitro experiments have suggested that SCF induces ckit þ CSC migration in a concentration dependent manner that could be antagonized by antibody against c-kit. Furthermore, the SCF-induced migration of c-kit þ CSCs to infarcted myocardium was blocked by the inhibition of p38-MARK in vivo (Kuang et al, 2008). These results suggest that the SCF/c-kit mediate migration of c-kit þ CSCs and that migration of stem cells induced by SCF/ckit and SDF-1/CXCR4 pathways may share downstream p38-MAPK signaling pathways.…”
Section: Stem Cell Factor/c-kitmentioning
confidence: 78%
See 2 more Smart Citations
“…In vitro experiments have suggested that SCF induces ckit þ CSC migration in a concentration dependent manner that could be antagonized by antibody against c-kit. Furthermore, the SCF-induced migration of c-kit þ CSCs to infarcted myocardium was blocked by the inhibition of p38-MARK in vivo (Kuang et al, 2008). These results suggest that the SCF/c-kit mediate migration of c-kit þ CSCs and that migration of stem cells induced by SCF/ckit and SDF-1/CXCR4 pathways may share downstream p38-MAPK signaling pathways.…”
Section: Stem Cell Factor/c-kitmentioning
confidence: 78%
“…Kuang et al (2008) have demonstrated that the expression of SCF is significantly increased in the region immediately adjacent to the infarct (the peri-infarct myocardium) following MI in rats. The authors of these studies found higher expression of SCF in peri-infarct regions associated with an accumulation of transplanted c-kit þ CSCs.…”
Section: Stem Cell Factor/c-kitmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the cells that adhere to the blood vessel endothelium, permeate the vessel walls to access the target tissue. With the help of SDF-1α, the secretion of more MMP-9, NO, and VEGF promote the mobilization of stem cells (Tang et al, 2007;Kuang et al, 2008;Gao et al, 2010;Huang et al, 2010;Takamiya et al, 2011). These paracrine factors, especially VEGF, are important for maintaining or improving normal vascular endothelial function.…”
Section: Discussionmentioning
confidence: 99%
“…SCF/c-KIT effects mediating cell migration also depend on the MAPK pathway via phosphorylation and activity of p38 (Kuang et al 2008); MEK/MAPK inhibitors reduced the response to c-KIT by 30% (Farini et al 2007). …”
Section: The Mapk Pathwaymentioning
confidence: 99%